2016
DOI: 10.1159/000447483
|View full text |Cite
|
Sign up to set email alerts
|

The Role of High Mobility Group Box 1 Protein in Interleukin-18-Induced Myofibroblastic Transition of Valvular Interstitial Cells

Abstract: Background: Increased levels of interleukin-18 (IL-18) and high mobility group box 1 protein (HMGB1) have been reported in patients with calcific aortic valve disease (CAVD). However, the role of IL-18 and HMGB1 in the modulation of the valvular interstitial cell (VIC) phenotype remains unclear. We hypothesized that HMGB1 mediates IL-18-induced myofibroblastic transition of VICs. Methods: The expression of IL-18, HMGB1 and α-smooth muscle actin (α-SMA) in human aortic valves was evaluated by immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A previous study has also demonstrated that nonrheumatic, calcified human aortic valves are characterized by increased IL-18 expression on immunohistochemistry [13]. The study of Wang et al [8] is important since it extends the current literature [13] and provides further support to the notion of IL-18 as a pivotal player in the pathogenesis of calcific aortic valve stenosis. …”
mentioning
confidence: 73%
See 4 more Smart Citations
“…A previous study has also demonstrated that nonrheumatic, calcified human aortic valves are characterized by increased IL-18 expression on immunohistochemistry [13]. The study of Wang et al [8] is important since it extends the current literature [13] and provides further support to the notion of IL-18 as a pivotal player in the pathogenesis of calcific aortic valve stenosis. …”
mentioning
confidence: 73%
“…In this issue of Cardiology , Wang et al [8] provide some interesting findings on the potential role of interleukin-18 (IL-18) and high-mobility group box 1 protein (HMGB1) in valvular calcification. They demonstrate that human calcific aortic valves express higher levels of IL-18/HMGB1 than noncalcified aortic valves [8].…”
mentioning
confidence: 99%
See 3 more Smart Citations